Methods for identification and differentiation of different Shewanella spp. isolates for diagnostic use. Issue 4 (27th December 2017) - Jung‐Schroers, V; Jung, A; Ryll, M; Bauer, J; Teitge, F; Steinhagen, D
Abstract: Shewanella spp. are Gram‐negative, rod‐shaped, motile bacteria that are widely distributed in marine and freshwater environments. The bacteria are present in the physiological microflora of fish from temperate waters and are known as fish spoilage species. From clinically healthy fish and from fish with skin ulcerations, Shewanella spp. is regularly isolated, indicating a possible role as fish pathogen. In this study, 74 isolates of Shewanella spp. were analysed. For species identification, biochemical techniques, 16S rRNA sequencing, MALDI‐TOF MS and the Sherlock Microbial Identification System (MIS) based on the composition of fatty acid ethyl esters were compared. The phylogenetic relationship, cytotoxicity in vitro and resistance against antibiotics were tested. The most reliable method for species identification was 16S rRNA sequencing. From diseased fish, clinically healthy fish and the aquatic environment, different Shewanella species were isolated. This indicates that Shewanella spp. is widespread in the aquatic milieu and acts as a secondary pathogen. The virulence of Shewanella spp. is probably not depending on the species but on the isolate itself. Many isolates of Shewanella spp. were showing multiresistances against antibiotic substances, especially in samples derived from retailers and in routine diagnostics, all Shewanella spp. should therefore be tested for resistances against antibiotic agents.